Does transformation of microfinance institutions achieve dual missions - Kim, Dae Hong (KDI School, 2015)
This study aims to assess the impact of institutional transformation of microfinance institutions (MFIs) on poverty alleviation and financial sustainability, using cross-country and panel data sets from the Microfinance Information Exchange (MIX) Market and the World Bank data. The analysis was conducted using pooled OLS with two-stage least squares (2SLS) and random effects regressions. In order to achieve this aim, the analysis was undertaken with respect to two criteria. On one hand, it examines whether the impact of transforming the legal status of MFIs from non-profits to for-profits on poverty alleviation; and on the other hand, from unregulated non-profits to regulated for-profits with regards to the dual missions: poverty reduction and financial sustainability. The results of the analysis suggest that, taking into account endogeneity with loans of MFIs, a country with higher loans from non-profits tends to have larger effects on reducing poverty than that of for-profits. With respect to regulation on MFIs, the net impact of unregulated non-profits on poverty alleviation is still larger than that of regulated for-profits. Especially, only the unregulated for-profits have a significant and positive impact on improving self-sustainability. This evidence implies that since unregulated non-profit MFIs, compared to regulated for-profit MFIs, more effectively reduce poverty with financially stable operation, the institutional transformation of MFIs should be carefully conducted in order to achieve a higher social impact of serving the poorest of the poor at a financially sustainable manner, helping them to overcome poverty.
Thesis(Master) --KDI School:Master of Development Policy,2015